Optimalisasi Limbah Sekam Padi Sebagai Briket Energi Dan Pemberdayaan Ekonomi Desa Ngampel: Studi Kasus di Desa Ngampel, Jombang - Miftachuddin, Achmad Agus Athok; Yuliana, Anggi Indah; Astiti, Lidya Dwi; Hardyanto, Mohamad David Wahyu Hardyanto (ABIDUMASY, 2025)
Ngampel Village in Ngusikan Sub-district, Jombang Regency, struggles with managing agricultural waste, particularly rice husks generated from rice production. Often underutilized, this waste contributes to environmental degradation. This community service initiative seeks to educate residents on transforming rice husks into briquettes as a sustainable energy source while enhancing the economic potential of agricultural byproducts. The project adopts a systematic method, including semi-carbonization, blending with binders, molding, and drying, to produce quality briquettes. This approach reduces environmental pollution from improper waste disposal, lowers fire risks, and encourages innovative resource use. Outcomes reveal heightened community awareness of sustainable waste management and increased interest in briquette production as a viable, eco-friendly energy option. This initiative underscores the value of community-driven innovation in tackling environmental issues and unlocking economic opportunities through agricultural waste utilization.